(untitled) (Journal of Advanced Veterinary and Animal Research, 2015)
The objectives of this study were to investigate the prevalence of gastrointestinal parasitism (GP), and to determine the effects of age, sex, breed, body score and body weight in the occurrences of GP of cattle in Banskhali Upazilla, Chittagong, Bangladesh. A total of 50 fecal samples were randomly collected directly from rectum of cattle. The samples were examined by routine coproscopical methods for the presence of different parasites and oocysts. Overall prevalence of GP infestation was 72% (n=36/50). Prevalence of Paramphistomum spp. infestation was found to be the highest (30%; n=15/50) followed by Toxocara spp. (12%; n=6/50), Fasciola spp. (10%; n=5/50), Oesophagostomum spp. (8%; n=4/50), Moniezia spp. (6%; n=3/50) and Trichostrongylus spp. (2%; n=1/50). Young cattle were mostly infested as compared to adult and calf. The results of this study provides an epidemiological forecast showing the prevalence of GP in cattle, which can be helpful for the clinician in diagnosis of such infections. http://dx.doi.org/10.5455/javar.2015.b113